The Urgency of Online Learning Media during the Covid-19 Pandemic at the Vocational School in Indonesia - Fahmi Huwaidi; Asep Bayu Dani Nandiyanto; Nazeri Muhammad (Indonesian Journal of Educational Research and Technology, 2021)
World Health Organization (WHO) has designated Covid-19 as a global pandemic because it has the opportunity to infect populations around the world. Therefore, in an effort to break the chain of spread of Covid-19, the Minister of Education and Culture issued a regulation on Learning during the pandemic, namely the learning process carried out remotely from home through online learning. This makes the use of social media or video conferencing an urgent matter to replace the learning system which is usually face-to-face method. In this study, we conducted research on understanding the urgency of the use of online learning media at vocational school. Experiments were done using online during student study services (namely Kuliah Kerja Nyata (KKN)). The effectiveness and understanding of students are the main focus in this research to create online learning that is effective, innovative, and creative.